2016
DOI: 10.18632/oncotarget.13425
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of 8p is an independent prognostic parameter in prostate cancer

Abstract: Deletion of chromosome 8p is the second most frequent genomic alteration in prostate cancer. To better understand its clinical significance, 8p deletion was analyzed by fluorescence in-situ hybridization on a prostate cancer tissue microarray. 8p deletion was found in 2,581 of 7,017 cancers (36.8%), and was linked to unfavorable tumor phenotype. 8p deletion increased from 29.5% in 4,456 pT2 and 47.8% in 1,598 pT3a to 53.0% in 931 pT3b-pT4 cancers (P < 0,0001). Deletions of 8p were detected in 25.5% of 1,653 Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 44 publications
0
44
0
Order By: Relevance
“…Even though our multivariate modeling suggested that 13q deletion testing may hold promise for a clinical test in preoperative situations, the prognostic significance of 13q deletion was rather limited and the risk of recurrence within 5 years differed only 10% between cancers with and without 13q deletion. This is less than previously observed for other deletions such as 10q (25% difference in the risk for PSA recurrence between PTEN deleted and undeleted cancers), 8p (20%) 6q (15%), 5q (15%), and 17p (10%) . However, it is possible that a combined analysis of several deletion loci (i.e., in order to determine a cancers deletion load) will lead to a better prediction of prognosis than analysis of single deletion loci.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Even though our multivariate modeling suggested that 13q deletion testing may hold promise for a clinical test in preoperative situations, the prognostic significance of 13q deletion was rather limited and the risk of recurrence within 5 years differed only 10% between cancers with and without 13q deletion. This is less than previously observed for other deletions such as 10q (25% difference in the risk for PSA recurrence between PTEN deleted and undeleted cancers), 8p (20%) 6q (15%), 5q (15%), and 17p (10%) . However, it is possible that a combined analysis of several deletion loci (i.e., in order to determine a cancers deletion load) will lead to a better prediction of prognosis than analysis of single deletion loci.…”
Section: Discussionmentioning
confidence: 74%
“…Our findings identify 13q deletion as a genomic alteration that is largely unrelated to ERG‐status. Using the same set of cancers we have previously identified a few other deletions, including loss of 12p and 8p that are unrelated to the ERG status.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations